Analisis Komparatif Overhead Kinerja CPU pada Lingkungan Bare Metal, Docker Container, dan KVM Virtual Machine Berbasis Linux Ubuntu - Ammanda Putri Nurhalizah; Ilham Nur Ramdani; Imelda Imelda (Institut Teknologi Garut, 2026)
Virtualization and containerization technologies are key solutions for improving the efficiency of modern computing infrastructure. This study aims to analyze a comparison of CPU performance overhead across three computing environments: Bare Metal, Docker Containers, and KVM Virtual Machines running on Ubuntu 24.04 LTS. Testing was conducted using Sysbench with the Events Per Second (EPS) metric as an indicator of throughput, with Bare Metal serving as the baseline. The results show that Docker Containers exhibit near-native performance with an overhead of -4.44%, indicating a slight performance improvement over the baseline due to efficient resource management. Conversely, the KVM Virtual Machine experienced a significant performance drop with an overhead of 81.78%. These findings suggest that containers are more efficient in utilizing CPU resources, while KVM Virtual Machines offer higher system isolation at the cost of reduced performance. This study provides a quantitative evaluation to serve as a basis for selecting computing technologies based on performance and isolation requirements.